Rethinking competitive advantage - Charan, Ram (Currency, 2020)
"How do you gain an edge in the digital age? In this lively, accessible guide, Ram Charan, bestselling author and advisor to some of the world's top CEOs, dissects the changing nature of competitive advantage, illustrating what it takes for companies--old and new alike--to compete against digital giants like Amazon, Alibaba, and Google. In today's business world, good strategy isn't just about preserving market share or building moats to ward off competitors. In the digital age, the most successful companies look at everything through a single lens: How can we create a better end-to-end consumer experience? As Jeff Bezos says, "When given the choice of obsessing over competitors or obsessing over customers, we always obsess over customers." Filled with behind-the-scenes stories of companies like Netflix, Amazon, Fidelity, and Alibaba, Rethinking Competitive Advantage highlights the tools these behemoths have relied on to reimagine customer experience and build competitive advantage: platform, data, and ecosystem. These companies don't just develop channels of distribution, they constantly crunch numbers, use algorithms to improve products, and create an ecosystem with outside sellers and their supply chain, where a stream of new innovations reinvigorates the customer's experience and creates new sources of revenue. Today's companies imagine market spaces that don't yet exist, ones with the potential to grow 10x or 100x--and they are willing to spend cash now on the promise of exponential profits down the road. To execute their objectives, these companies build strong, nimble, team-centered workforces that upend traditional hierarchy, forming a "social engine" that drives innovation under visionary leaders. Whether you're in the C-Suite of a Fortune 500 company or brainstorming the next digital start-up from your garage, Rethinking Competitive Advantage is the ultimate primer on competitive advantage today, revealing the "secret sauce" behind some of the world's leading companies--and showing you what you must do to compete"--